Analysis of Indigenous Communication Channels for Disseminating Agricultural Information: The case of North Gondar Zone (International Journal of Scientific Research and Management (IJSRM), 2018)
In Ethiopia, information reaches to farmers mainly through indigenous and exogenous communication channels which include social gatherings, training, meetings, and conferences followed by learning through direct observation. Indigenous communication channels provides an effective means for rural communities to access various types of information related to their farming and day-to-day life. However, the practices and prospects of indigenous communication channels need policy-oriented research to analyze and facilitate meaningful interventions in the areas of agricultural information dissemination. This study was initiated with the objective of identifying existing indigenous Communication Channels used by farm households, assess farmers perception of indigenous Communication Channels utilization to exchange agricultural innovation, analyze the challenges related to exchanging and disseminating of agricultural information with respect to indigenous knowledge and assess indigenous agricultural knowledge preservation practices in the North Gondar Zone. Data were collected from 120 sample household heads, 30 focus group discussants and key informants and both primary and secondary data were used for the study. Household survey, focus group discussion and key informant interview were used to triangulate and strengthen the data collected sample household heads. For the purpose of data analysis, descriptive statistics (frequency & percentage), and inferential statistics (chi-square test T-test) were used. The results of the study showed that 70% of the respondents highly preferred indigenous communication channels than exogenous communication channels. The most regularly preferred and utilized channel was Church (47.5%), followed by public meeting organized by the community (22.5%) where as village meeting organized by the community (11.7%) and neighbors (6.7%) occupied the third and fourth position in the ranking. It was also indicated that the utilization of indigenous communication channels determined by age and educational status of respondents. In this regard elder and illiterate household heads preferred and utilized indigenous communication channels than exogenous communication channels. Based on the findings, the researchers recommended that indigenous communication channels utilization should be incorporated in the plan of Agricultural Extension Agents, indigenous communication channels should be form as part of agricultural information dissemination package to encourage and facilitate exchanging of information by rural people, Policies, strategies and good practices with respect to indigenous communication channels have to be developed with active participation of primary stakeholders to utilize it effectively.